Plasmodium sporozoite motility is modulated by the turnover of discrete adhesion sites - Münter, Sylvia; Sabass, Benedikt; Kudryashev, Mikhail; Hegge, Stephan; Engel, Ulrike; Matuschewski, Kai; Schwarz, Ulrich S.; Frischknecht, Friedrich (Cell host and microbe, 2009)
Sporozoites are the highly motile stages of the malaria parasite injected into the host's skin during a mosquito bite. In order to navigate inside of the host, sporozoites rely on actin-dependent gliding motility. Although the major components of the gliding machinery are known, the spatiotemporal dynamics of the proteins and the underlying mechanism powering forward locomotion remain unclear. Here, we show that sporozoite motility is characterized by a continuous sequence of stick-and-slip phases. Reflection interference contrast and traction force microscopy identified the repeated turnover of discrete adhesion sites as the underlying mechanism of this substrate-dependent type of motility. Transient forces correlated with the formation and rupture of distinct substrate contact sites and were dependent on actin dynamics. Further, we show that the essential sporozoite surface protein TRAP is critical for the regulated formation and rupture of adhesion sites but is dispensable for retrograde capping.